1982
DOI: 10.1002/ar.1092030206
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of progesterone in the uterus, broad ligament, and uterine arteries of beef cows

Abstract: Samples of uterine horn, broad ligament (mesosalpinx and mesometrium), and uterine artery of ten unilaterally ovulating cows, 12-15 days after mating, were examined for differences in concentration of progesterone. Tissues (mesosalpinx, branches of the uterine artery, anterior uterine horn) adjacent to the ovary bearing the corpus luteum contained significantly greater quantities of progesterone than more distal tissues (mesometrium, uterine artery, posterior uterine horn) on the same side and all tissues on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 14 publications
(4 reference statements)
2
30
1
1
Order By: Relevance
“…The reason for this expression gradient in the luteal phase sheep remains unknown but may relate to local hormone gradients within the uterine tissues. Pope et al (34) and Weems et al (43,44) demonstrated in unilaterally ovulating sheep and cattle that the uterine tissue and artery on the side ipsilateral to the corpus luteum contained greater quantities of progesterone than those more distal. The ability of progesterone to be concentrated in the uterine tissues occurs via a countercurrent exchange of steroid between the ovarian vein to the ovarian artery (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this expression gradient in the luteal phase sheep remains unknown but may relate to local hormone gradients within the uterine tissues. Pope et al (34) and Weems et al (43,44) demonstrated in unilaterally ovulating sheep and cattle that the uterine tissue and artery on the side ipsilateral to the corpus luteum contained greater quantities of progesterone than those more distal. The ability of progesterone to be concentrated in the uterine tissues occurs via a countercurrent exchange of steroid between the ovarian vein to the ovarian artery (42).…”
Section: Discussionmentioning
confidence: 99%
“…A gradient of progesterone concentrations (34,43,44) and estrogen receptor densities (25) have also been observed in the uterine and aortic vasculatures, respectively. These steroid hormones are known to regulate…”
mentioning
confidence: 96%
“…However, concentrations were 6-to 13-fold higher in uterine fluid on day 15 compared to all the other days and concentrations in the uterine horn ipsilateral to the corpus luteum were over 2-fold higher than those in the contralateral side. The concentration of progesterone is known to be higher in the tissue (Pope et al, 1982) and uterine horn ipsilateral to the corpus luteum in cattle while Weems et al (1988) have shown that the concentration of progesterone in the ipsilateral uterine vein is almost 2-fold higher than that in the contralateral vein, which was in turn similar to the concentration in jugular venous blood. Based on these data, it is tempting to conclude that the concentration of uterine RBP is sensitive to the concentrations of systemic progesterone.…”
Section: Direct Effectmentioning
confidence: 92%
“…Indeed, P4 concentration on tissues (mesosalpinx, uterine artery, ovarian artery, anterior and posterior region of uterine horn) in the ipsilateral horn was greater than in the opposite side in beef and dairy cows and in ewes MAURER;STORMSCHAK, 1982;WEEMS et al, 1988WEEMS et al, , 1989. Also the uterine and ovarian artery adjacent to the ovary bearing the CL had higher P4 concentration (WEEMS et al, 1988(WEEMS et al, , 1989.…”
Section: The Effect Of Side Of the Uterine Horn Relative To The Ovarymentioning
confidence: 95%
“…Porém, Reichenbach et al (1992) demonstrou que as taxas de prenhez são similares em transferências de um ou dois embriões no corno ipsolateral ao CL e transferência de um embrião em cada corno uterino. Estudos envolvendo a distribuição espacial de moléculas ao longo do trato reprodutivos de fêmeas já foram realizados em vacas MAURER;STORMSHAK, 1982;BAUERSACHS et al, 2005;DEAVER et al, 2013), ovelhas (MEIKLE et al, 1997(MEIKLE et al, , 2001, ratos (HICKEY;…”
Section: Introductionunclassified